First report and multilocus genotyping of Enterocytozoon bieneusi from Tibetan pigs in southwestern China - Luo Run; Xiang Leiqiong; Liu Haifeng; Zhong Zhijun; Liu Li; Deng Lei; Liu Ling; Huang Xiangming; Zhou Ziyao; Fu Hualin; Luo Yan; Peng Guangneng (Parasite, 2019)
Enterocytozoon bieneusi is a common intestinal pathogen in a variety of animals. While E. bieneusi genotypes have become better-known, there are few reports on its prevalence in the Tibetan pig. This study investigated the prevalence, genetic diversity, and zoonotic potential of E. bieneusi in the Tibetan pig in southwestern China. Tibetan pig feces (266 samples) were collected from three sites in the southwest of China. Feces were subjected to PCR amplification of the internal transcribed spacer (ITS) region. Enterocytozoon bieneusi was detected in 83 (31.2%) of Tibetan pigs from the three different sites, with 25.4% in Kangding, 56% in Yaan, and 26.7% in Qionglai. Prevalence varies according to age group, from 24.4% (age 0–1 years) to 44.4% (age 1–2 years). Four genotypes of E. bieneusi were identified: two known genotypes EbpC (n = 58), Henan-IV (n = 24) and two novel genotypes, SCT01 and SCT02 (one of each). We compare our results with a compilation of published results on the host range and geographical distribution of E. bieneusi genotypes in China. Phylogenetic analysis showed these four genotypes clustered to group 1 with zoonotic potential. Multilocus sequence typing (MLST) analysis of three microsatellites (MS1, MS3, MS7) and one minisatellite (MS4) was successful in 47, 48, 23 and 47 positive specimens and identified 10, 10, 5 and 5 genotypes at four loci, respectively. This study indicates the potential danger of E. bieneusi to Tibetan pigs in southwestern China, and offers basic advice for preventing and controlling infections.